IMPLEMENTASI TEKHNIK KONSELING ALUR CURHAT DALAM MENINGKATKAN STUDENT WELLBEING DI PESANTREN - Rizmatulla`aliz Zakiyah; Lailatul Fitriyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is motivated by the limited attention to students’ wellbeing in Islamic boarding schools, which tend to emphasize cognitive and spiritual aspects, while academic pressure, social dynamics, and environmental adaptation often lead to psychological challenges among students. This research aims to analyze the implementation of the CURHAT counseling technique in improving student wellbeing in the Al-Mawaddah area of Nurul Jadid Islamic Boarding School. The study employs a qualitative approach with a case study design, utilizing observation, in-depth interviews, and documentation as data collection techniques, and analyzed using the Miles and Huberman model. The findings reveal that the CURHAT counseling technique, implemented through structured stages including chemistry, case disclosure, empathic response, solution formulation, alternative solutions, and follow-up, significantly enhances students’ emotional openness, self-regulation, and learning motivation. Furthermore, the responsive and humanistic counseling approach creates a safe space for students to express their concerns honestly and actively participate in problem-solving. The implications of this study indicate that the CURHAT counseling technique can serve as an effective, adaptive, and contextual counseling model to promote psychological wellbeing among students in Islamic boarding schools.